Técnicas de otimização aplicadas à operação de sistemas de telefonia móvel celular GSM. - Samuel Albasini Langa (2005)
The pronounced increase in the number of telecommunication users nowadays has indicated that a better approach, in terms of cost, would be to optimize the working plant instead of starting physical expansions of the network. In the present master thesis the operation of GSM celular mobile networks is considered. The GSM networks are among the most popular celular mobile telephony systems in the world. The number of services offered by GSM have been increasing, incorporating more and more functionalities, as it can be clearly seen since the advent of GPRS networks. In the GSM systems, optimization techniques can be applied to the problems of frequency hoping and determination of the optimum number of guard channels and the total number of channels in cell clusters. Such techniques are considered in this work. In each case numerical results, obtained from simulations, algorithms analyses and improvement propostions are presented.